Back Cover: Droplet Precise Self‐Splitting on Patterned Adhesive Surfaces for Simultaneous Multidetection (Angew. Chem. Int. Ed. 26/2020). Issue 26 (28th April 2020) - Li, Huizeng; Fang, Wei; Zhao, Zhipeng; Li, An; Li, Zheng; Li, Mingzhu; Li, Qunyang; Feng, Xiqiao; Song, Yanlin
Abstract : The precise separation and localization of microdroplets are fundamental for various fields such as biological screening, combinatorial analysis, and complex sample recognition. In their Research Article on page 10535, M. Li, Q. Li, Y. Song, and co‐workers demonstrate a droplet self‐splitting strategy to generate mutually independent microdroplets with well‐defined morphology and arrangement, and achieve the simultaneous multiple detection of complex analytes using one droplet of sample.